2018
DOI: 10.1111/trf.14503
|View full text |Cite
|
Sign up to set email alerts
|

Implanted vascular access device options: a focused review on safety and outcomes

Abstract: Implantable vascular access devices are frequently used in patients who have poor peripheral venous access. These devices can be partially implanted as tunneled and nontunneled central catheters, or they can be fully implanted as ports. Compared with long-term catheters, implanted ports have lower infection rates and improved perceptions of quality of life, but complications still occur in 2% to 18% of patients, frequently requiring removal of the device. Since the conception of implantable vascular access dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 54 publications
3
21
1
2
Order By: Relevance
“…Our complication rate was also very low (0.8%) with only a single catheter associated thrombosis identified across our 9 patients and 124 RCE procedures and no associated infections. While we did not see any thromboses during the first year of our study while tPA usage was not standard protocol, its regular use over the last 2 years of our study may have played a role in our lower than expected complication rate (2‐18% reported from other studies) …”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Our complication rate was also very low (0.8%) with only a single catheter associated thrombosis identified across our 9 patients and 124 RCE procedures and no associated infections. While we did not see any thromboses during the first year of our study while tPA usage was not standard protocol, its regular use over the last 2 years of our study may have played a role in our lower than expected complication rate (2‐18% reported from other studies) …”
Section: Discussioncontrasting
confidence: 53%
“…While we did not see any thromboses during the first year of our study while tPA usage was not standard protocol, its regular use over the last 2 years of our study may have played a role in our lower than expected complication rate (2-18% reported from other studies). 10 Limitations of this study include its retrospective nature and small-moderate size. Because we only had 9 patients enrolled there is a possibility that differences in individual patients were enough to create differences present between the port types or mask possible benefit of tPA use.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Unfortunately, VADs are associated with increased risks, including bloodstream infections (BSIs), fibroblastic sleeves/thromboses, migration of catheter tip, and other mechanical failures . VADs are the most significant source of health care–associated BSIs, accounting for up to 500,000 BSIs each year in the United States .…”
mentioning
confidence: 99%